2022
DOI: 10.1155/2022/7333005
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Downstream Separation of Itaconic Acid Using Carbon-Based Adsorbents

Abstract: Separation of itaconic acid from aqueous solution has been explored using various carbon-based adsorbents obtained from the pyrolysis and KOH activation of coconut shell biomass. The best preparation conditions to obtain a tailored adsorbent for itaconic acid purification were identified via a Taguchi experimental design, where its adsorption properties were maximized. The best activated carbon was obtained via coconut shell pyrolysis at 750 °C for 4 h plus an activation with 0.1 KOH and a final treatment at 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…While in the sugar industry, decolorization is usually implemented using anion exchange resins [ 77 , 78 ], decolorization in organic acid production is most commonly realized by adding activated charcoal [ 22 , 79 , 80 , 81 ]. However, similar to other carboxylic acids, ITA can adsorb at both types of these decolorization agents, reducing process yield and thereby economic feasibility [ 82 ] ( Section 3.1.1 ). In this work, the potential yield loss is minimized by two measures.…”
Section: Resultsmentioning
confidence: 99%
“…While in the sugar industry, decolorization is usually implemented using anion exchange resins [ 77 , 78 ], decolorization in organic acid production is most commonly realized by adding activated charcoal [ 22 , 79 , 80 , 81 ]. However, similar to other carboxylic acids, ITA can adsorb at both types of these decolorization agents, reducing process yield and thereby economic feasibility [ 82 ] ( Section 3.1.1 ). In this work, the potential yield loss is minimized by two measures.…”
Section: Resultsmentioning
confidence: 99%
“…They also introduce a lot of micropores into the structure. In addition, these techniques can produce diverse morphologies such as nanofibers, nanoparticles, nanosheets, and nanotubes in porous materials, which can meet all the needs of industrial applications [31][32][33]. It has been found that the performance of mesoporous materials in the various fields is affected mainly by structural properties such as the specific surface area, pore size, pore structure, and heteroatoms doping, such as nitrogen (N), phosphorus (P), sulfur (S), and boron (B) [34].…”
Section: Introductionmentioning
confidence: 99%
“…In wastewater treatment, the electrostatic interaction between the ionized functional groups of pollutants and the surface functional groups of biomass-derived carbon can be observed during adsorption, where pH value can affect the electrostatic force. [279] Guo et al [244] concluded in a study that triggering factors for the enhancement of adsorption capacity include electrostatic attraction. Under alkaline conditions, the electrostatic force between Mg 2+ and negatively charged active carbon ensured its stable and high adsorption capacity.…”
Section: Electrostatic Interactionsmentioning
confidence: 99%